MENINGKATKAN AKTIVITAS BELAJAR SISWA POKOK BAHASAN TEKS NARRATIVE MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DI KELAS XI IPS-3 SMA NEGERI 2 LUBUK PAKAM TAHUN PELAJARAN 2019/2020 - Kasmawati Kasmawati (Universitas Negeri Medan, 2021)
Abstract: Improving Student Learning Activities on the subject of Narrative Texts through the Numbered Head Together (NHT) Learning Model in Class Xi Ips-3 Sma Negeri 2 Lubuk Pakam for the 2019/2020 academic year. This study aims to see student learning activities and student outcomes when working in groups in class on English subjects with the Number Head Together (NHT) learning model in class XI IPS-3 SMA Negeri 2 Lubuk Pakam. The subjects of this study were taken in class XI IPS-3 SMA Negeri 2 Lubuk Pakam with a total of 30 students. At the beginning of the KBM, a learning outcome test (Pretest) was carried out with an average data of 52.3, this shows that on average students rarely read books before learning at school. Then continued with KBM, at the end of the second and fourth KBM, the Formative I and Formative II learning outcomes tests showed 60.0 and 80.6, respectively. Looking at the data, there was an increase in student learning outcomes after applying the Number Head Together learning model and these changes were due to the teacher's actions during the KBM in Cycle II. Student activity data according to observer observations in Cycle I include writing/reading (35%), working (24%), asking fellow friends (1 3%), asking the teacher (13%), and those that are not relevant to KBM (16 %). The data on student activity according to observations in Cycle II included writing/reading (21%), working (32%), asking friends (24%) asking the teacher (19%), and those not relevant to teaching and learning (4%). There was an increase in student learning activities by applying the Number Head Together learning model in class XI IPS-3 SMA Negeri 2 Lubuk Pakam. By applying the Number Head Together learning model, student activity in learning and learning outcomes can increase.Keywords: Number Head Together Learning Model, Learning Activities Abstrak: Meningkatkan Aktivitas Belajar Siswa Pokok Bahasan Teks Narrative Melalui Model Pembelajaran Numbered Head Together (Nht) Di Kelas Xi Ips-3 Sma Negeri 2 Lubuk Pakam Tahun Pelajaran 2019/2020. Penelitian ini bertujuan untuk melihat aktivitas belajar siswa dan hasil siswa saat bekerja dalam kelompok dikelas pada mata pelajaran Bahasa Inggris dengan model pembelajaran Number Head Together (NHT) di kelas XI IPS-3 SMA Negeri 2 Lubuk Pakam. Subjek penelitian ini diambil di kelas XI IPS-3 SMA Negeri 2 Lubuk Pakam dengan jumlah siswa 30 orang. Awal KBM dilakukan tes hasil belajar (Pretes) dengan data rata-rata 52,3 hal tersebut menunjukkan bahwa rata-rata siswa jarang membaca buku sebelum pembelajaran disekolah. Kemudian dilanjutkan KBM, akhir KBM ke II dan KBM ke IV dilakukan tes hasil belajar Formatif I dan Formatif II hasilnya masing-masing menunjukkan 60,0 dan 80,6. Melihat data tersebut, Terjadi peningkatan hasil belajar siswa setelah menerapkan model pembelajaran Number Head Together dan perubahan tersebut akibat tindakan guru selama KBM pada Siklus II. Data aktivitas siswa menurut pengamatan pengamat pada Siklus I antara lain menulis/membaca (35%), bekerja (24%), bertanya sesama teman (1 3%), bertanya kepada guru (13%), dan yang tidak relevan dengan KBM (16%). Data aktivitas siswa menurut pengamatan pada Siklus II antara lain menulis/membaca (21%), bekerja (32%), bertanya sesama teman (24%) bertanya kepada guru (19%), dan yang tidak relevan dengan KBM (4%). Terjadi peningkatan aktivitas belajar siswa dengan menerapkan model pembelajaran Number Head Together di kelas XI IPS-3 SMA Negeri 2 Lubuk Pakam. Dengan menerapkan model pembelajaran Number Head Together keaktifan siswa dalam pembelajaran dan hasil belajarnya dapat meningkat. Kata Kunci : Model Pembelqjaran Number Head Together, Aktivitas Belajar